Influence of the magneto-optic effects on a light self-focusing in Kerr media - Rutkowska, Katarzyna Agnieszka; Jasiński, Jerzy; Świtkowski, Krzysztof; Malomed, Boris; Morandotti, Roberto (Photonics Letters of Poland, 2012)
We present the possibility of light beam-propagation control in a Kerr nonlinear medium through the efficient management of magnetically-induced linear and circular birefringences. Theoretical analyses, performed by dint direct numerical simulations of modified nonlinear Schrödinger equation, as well as by means of variational approximation, show consistent results. Full Text: PDF References R.W. Boyd, Nonlinear optics (San Diego, Academic Press 2008). C. Sulem, P.L. Sulem, The nonlinear Schrödinger equation: self-focusing and wave collapse (New York, Springer 1999) Y.S. Kivshar, D.E. Pelinovsky,"Self-focusing and transverse instabilities of solitary waves", Phys. Rep. 331, 117 (2000)[CrossRef] R. Kurzynowski, W.A. Woźniak,"Superposition rule for the magneto-optic effects in isotropic media", Optik 115, 473 (2004)[CrossRef] B.A. Malomed,"Chapter 2 Variational methods in nonlinear fiber optics and related fields", Progr. Optics 43, 71 (2002)[CrossRef] K.A. Rutkowska, B.A. Malomed, R. Morandotti,"Control of the collapse of bimodal light beams by magnetically tunable birefringences", Opt. Express 18, 8879 (2010)[CrossRef]